PEMANFAATAN KAMERA LUBANG JARUM PADA PEMBELAJARAN SENI BUDAYA BAGI SISWA SEKOLAH DASAR: IMPLEMENTASI KETERAMPILAN ABAD 21 - Briliyan Syarifudin Ahmad (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2021)
This article aims to present the results of a study on the utilization of pinhole camera as an alternative media of learning to implement 21st century skills in arts and culture learning in the primary schools through-the activities of making cameras, decorating cameras, taking pictures, and presenting pictures. Literature review is carried out to collect information on 21st century skills and the utilization of pinhole camera in the process of learning arts and culture in primary schools. The discussion puts forward students’ activities in the process of making pinhole camera, using the camera, and doing collaboration with other learning subjects. The result of the study comes up with the ideas of creating alternative learning materials and media through the utilization of pinhole camera which enables teachers to design contented and meaningful learning for students. Subsequently, this may remarkably substantiate the implementation of 21st century skills at schools in actual practices of problem solving, developing creativity, collaboration, and communication, to successfully achieve the learning objectives.